'Managing successful change in the public sector': a view from the consultants' world. Issue 4 (3rd April 2018) - Fattore, Giovanni; Iacovone, Donato; Steccolini, Ileana
ABSTRACT: Our paper presents the results of a survey on the perceptions of 680 Italian public-sector consultants on the drivers of successful organizational change according to Fernandez and Rainey's model. The results show that the consultants mostly confirm the model, though recognizing that the various drivers have different degrees of relevance. A clear vision and plan for change and the top management's commitment are seen as central in change processes, whereas interestingly, resource availability and a comprehensive approach to change appear to play a less relevant role.